General view of Vienna from St. Charles Church - Piringer, Benedikt, 1780-1826 (engraver):::Creator::::::::::::; Janscha, Laurenz, 1749-1812 (artist):::Contributor::::::::::::; Laborde, Alexandre Louis Joseph de, 1774-1842 (author)::::::::::::::: (Didot)
Aquatint engraving with a panoramic view of Vienna